Women oppression and emancipation through application of amazonian and masculinist theories in selected novels by Nawal El Saadawi and Buchi Emecheta - Abdulrahaman, Abdulwaheed Idris (2020)
Most researchers in the area of feminist discourse have focused predominantly on patriarchal oppression on women, socio-cultural, political, economic, racial and religious oppression on women. Attention has mainly been on the extraneous factors that bring about oppression and discontentment to the lives of the women. This current study focuses on women oppression by exploring the various aspects of maternal oppression on women as presented in the selected novels of Nawal El Saadawi (Egypt) and Buchi Emecheta (Nigeria). The two female novelists have been chosen for this study due to the sameness in their ideological pursuit of maternal oppression on women and the strategy for emancipation as distinct from their contemporaries who equally focus on women oppression but from extraneous perspective. This current study therefore, focuses on women’s active contribution on the oppression, suppression, and brutality of their fellow women. The oppressive tendencies executed on the female victims by their fellow women resulted in misery, prostitution, perpetual unhappiness and untimely death of the oppressed women. This aspect has hardly been explored. This current study, through a textual analysis, intends to fill the gap by examining selected novels of two female novelists from Egypt and Nigeria through application of Amazon feminism of Thomas Gramstad (1999) and its concepts of Androgyny, or masculine-feminine duality of gender and Masculinist theory of Chinweizu (1990) and its concepts of mother power, bride power and wife power. The study examines selected novels of Nawal El-Saadawi’s Memoirs of a Woman Doctor (1989), A Daughter of Isis (2002), and Woman at Point Zero (2015) and Buchi Emecheta’s Second Class Citizen (1975), The Bride Price (2013) and The Joy of Motherhood (2013). The study aims to investigate how maternal oppression on women is perpetrated in the selected novels using the concepts of mother power, bride power and wife power as espoused in the Masculinist theory of Chinweizu. I aim to explore the representation of female characters as the primary architects of their fellow women’s oppression within the patriarchal set-ups by employing Chinweizu’s Masculinist theory and its concepts as analytical tools. Lastly, the study aims to discover how the oppressed female characters reappraised their oppressed selves, which leads to their emancipation by applying Thomas Gramstad’s Amazon feminism and its concept of “androgyny”. The study highlights the different forms of matriarchal oppression on women, which are in the forms of female genital mutilation, preference for the male in all social matters, and showing rejection in all matters relating to the female. In this study, the role of androgyny is examined as the most suitable virtues required for the attainment of the goal of gender equality and emancipation of the oppressed female characters. The study further stresses that despite the perennial oppression of women as evidently portrayed in the selected novels, with determined reappraisal, the oppressed androgynous heroines have been able to change their oppressed status and attained emancipation. Further studies could be conducted on women’s fictional narratives from East and South Africa to authenticate whether or not the phenomenon of matriarchal oppression on women is prevalent in other parts of the African continent.